Effect of Nickel on Density and Surface Tension of Liquid Tin - Mudryi, S.I.; Lytvyn, M.A. (Physics and Chemistry of Solid State, 2015)
Density and surface tension for Sn1-xNix(x = 0; 0,05; 0,1) have been measured by means of sessile drop method. Temperature dependences of these parameters as well as influence of Ni-atoms on density and surface tension were analyzed. It is shown that chemical ordering is one of the most important factor, determining surface properties and density.